Pemberdayaan Kelompok Wanita Tani Migunani Kulon Progo Melalui Tumpangsari Tanaman Jagung Manis Kedelai Sayur Berbasis Nir Limbah - Eska Stefani; Ignasius Suprih Sudrajat; Darnawi Darnawi; Evi Setiawati (Universitas Widya Mataram, 2025)
This community service program aimed to empower the Migunani Women Farmers Group (KWT) in Donomulyo Village, Nanggulan, Kulon Progo, through the implementation of intercropping syste, of sweet corn and vegetable soybeans based on zero-waste farming practices. The program employed two main methods: socialization and participatory mentoring over six months, involving 35 members of the group. The socialization stage focused on the concepts of incropping and the utilization of crop residus as organic fertilizer, while mentoring activities included demonstration plots and field monitoring. The results showed that the intercropping system implroved lan-use efficiency and produced 485 kg of sweet corn and 420 kg of green fodder from 400 m2 of land. This initiative not only enhanced the income and economic independence of women farmers but also fostered awerness of sustainable agriculture through zero-waste practices. The empowerment model developed in this program has strong potential to be replicated by other farmer groups in the Kulon Progo region.